Synthesis and characterization of chitosan based sponges for wound dressings - Matsvaire, Taguma Noble (Stellenbosch : Stellenbosch University, 2017)
ENGLISH ABSTRACT: The work presented in this study focused on the development of chitosan based sponges for the possible use as wound dressings. The sponges were to be modified to try and overcome some of the flaws associated with the use of natural polymers, that is, the poor mechanical properties. The important parameters that had to be met were a continuously porous morphology, to have a good absorption capability, good thermal properties, increase the mechanical strength and to maintain and/or increase the antimicrobial properties inherently in the chitosan. The two crosslinking agents that were used in this study to crosslink the chitosan sponges were genipin and tannic acid (TA). These are both natural crosslinking agents as this provided a platform to create a possible non-toxic wound dressing. The mechanical properties of the chitosan sponges resulting from these two crosslinking agents were compared to that when a synthetic crosslinking agent, namely glutaraldehyde (glut), was used. In an attempt to further enhance the mechanical properties, microcrystalline cellulose (MCC) was incorporated into the sponges as a reinforcing agent. The antimicrobial nature of a wound dressing is of high importance as it aids the healing processes in wounds. Certain properties that were imparted on the sponges by the different synthesis parameters were analysed in order to determine how to best enhance these properties as they play a vital role in the wound healing process. The sponges were synthesized using the bubbling technique and freeze–drying. The temperature used during the synthesis was of importance as the interaction between the chitosan and the crosslinking agents differs at different temperatures. The time taken to crosslinking time allowed during synthesis of the sponges was also of significance as this variable also had an important influence on the resultant properties of the sponges. The crosslinking of the sponges was confirmed using FTIR spectroscopy where the characteristic shifts and peaks that have occurred due to the crosslinking could be seen. These shifts are due to the chemical reactions that occur when the chitosan and the crosslinking agents react. The morphology of the sponges was determined using SEM where the porosity of the sponges could then be analysed and gave better understanding of some of certain other properties. The homogeneous distribution of MCC in the chitosan sponges was confirmed using confocal microscopy. The thermal properties of all the sponges were investigated using TGA and DSC. The TGA and DSC results showed that the crosslinking using either genipin or TA improved the thermal properties of the sponges. Absorbance tests were done to determine the absorption properties of the sponges which were also improved by the crosslinking when using either one of the involved crosslinking agents. For testing of the mechanical strength, compressional tests were done and these showed that there was an increase in the strain percentage in comparison to the uncrosslinked sponges but was, however, less than those for the sponges crosslinked with glutaraldehyde. The antimicrobial properties of the samples were analysed using the alamar assay technique. This assay showed that the antimicrobial properties were sensitive to crosslinking temperature, MCC loadings, Gramicidin S treatment and the crosslinking agent used. The samples crosslinked with genipin at 0.5 weight percent concentrations showed the greatest enhancement in antimicrobial properties.